Optimizing Payroll Accounting Information System at West Serang Tax Service Office: A Case Study - Faris Nurul Yaqin; Dabella Yunia (Journal of Applied Business, Taxation and Economics Research, 2023)
This study aims to determine whether the employee payroll accounting information system at the West Serang Pratama Tax Service Office. The research method used is descriptive method. The types of data used are primary data and secondary data. Data collection methods used are observation methods, interview methods, and literature methods. The employee payroll accounting information system at the West Serang Primary Tax Service Office is in accordance with the Standard Operational Procedure issued by the Directorate General of Taxes which is under the auspices of the Ministry of Finance of the Republic of Indonesia as a whole almost in accordance with the Standard Operational Procedure, this shows that the employee payroll accounting information system at The West Serang Pratama Tax Service Office has been implemented properly.